Microglial activation contributes to cognitive impairments in rotenone-induced mouse Parkinson’s disease model - Dongdong Zhang (Journal of Neuroinflammation, 2021)
Abstract Background Cognitive decline occurs frequently in Parkinson’s disease (PD), which greatly decreases the quality of life of patients. However, the mechanisms remain to be investigated. Neuroinflammation mediated by overactivated microglia is a common pathological feature in multiple neurological disorders, including PD. This study is designed to explore the role of microglia in cognitive deficits by using a rotenone-induced mouse PD model. Methods To evaluate the role of microglia in rotenone-induced cognitive deficits, PLX3397, an inhibitor of colony-stimulating factor 1 receptor, and minocycline, a widely used antibiotic, were used to deplete or inactivate microglia, respectively. Cognitive performance of mice among groups was detected by Morris water maze, objective recognition, and passive avoidance tests. Neurodegeneration, synaptic loss, α-synuclein phosphorylation, glial activation, and apoptosis were determined by immunohistochemistry and Western blot or immunofluorescence staining. The gene expression of inflammatory factors and lipid peroxidation were further explored by using RT-PCR and ELISA kits, respectively. Results Rotenone dose-dependently induced cognitive deficits in mice by showing decreased performance of rotenone-treated mice in the novel objective recognition, passive avoidance, and Morris water maze compared with that of vehicle controls. Rotenone-induced cognitive decline was associated with neurodegeneration, synaptic loss, and Ser129-phosphorylation of α-synuclein and microglial activation in the hippocampal and cortical regions of mice. A time course experiment revealed that rotenone-induced microglial activation preceded neurodegeneration. Interestingly, microglial depletion by PLX3397 or inactivation by minocycline significantly reduced neuronal damage and α-synuclein pathology as well as improved cognitive performance in rotenone-injected mice. Mechanistically, PLX3397 and minocycline attenuated rotenone-induced astroglial activation and production of cytotoxic factors in mice. Reduced lipid peroxidation was also observed in mice treated with combined PLX3397 or minocycline and rotenonee compared with rotenone alone group. Finally, microglial depletion or inactivation was found to mitigate rotenone-induced neuronal apoptosis. Conclusions Taken together, our findings suggested that microglial activation contributes to cognitive impairments in a rotenone-induced mouse PD model via neuroinflammation, oxidative stress, and apoptosis, providing novel insight into the immunopathogensis of cognitive deficits in PD.